Otimização : estudo de máximos e mínimos de funções que definem problemas cotidianos - Ferreira, Thed Freitas (2018)
In the present work, the objective is to present a study on the methods of optimization and to apply them in the solution of daily problems. In mathematics, optimization refers to the study of problems in which one wants to maximize or minimize a given function by systematically choosing the values of variables within a viable set. We can analyze optimization problems by di erentiability with and without constraints, introducing the Lagrange multiplier method. The resolutions presented, based on a small theoretical basis, are concerned to cover di erent approaches and provide the relationship of concepts. One of the methods to determine the maximum and minimum of functions is to use the calculation in several variables, which will be approached in this work. Possible situations related to everyday life are presented so that the optimization process can be approached by high school students.